Antimicrobial treatment of Mycoplasma hyopneumoniae infections. (May 2020) - Maes, Dominiek; Boyen, Filip; Haesebrouck, Freddy; Gautier-Bouchardon, Anne V.
Highlights: Many classes of antimicrobials show activity against M. hyopneumoniae ( M. hp ). Tetracyclines, macrolides, lincosamides and pleuromutilins are commonly used. Florfenicol, aminoglycosides and aminocyclitols are also used. Treatment improves health parameters and reduces performance losses. Acquired resistance of M. hp strains to some antibiotics has been reported. Abstract: Mycoplasma hyopneumoniae ( M. hyopneumoniae ) is the primary agent of enzootic pneumonia, a chronic and economically important respiratory disease of pigs. Control and prevention of M. hyopneumoniae infections can be accomplished by optimization of management and housing conditions, and by vaccination. The present paper summarizes the current knowledge on the main characteristics and efficacy of antimicrobials used for the treatment of clinical M. hyopneumoniae infections, the in vitro and in vivo activities of these antimicrobials and the reported resistance mechanisms against some. Potentially active antimicrobials against M. hyopneumoniae include tetracyclines, macrolides, lincosamides, pleuromutilins, amphenicols, aminoglycosides, aminocyclitols and fluoroquinolones. Antimicrobial treatment can be administered either orally or parenterally. Based on the overall results of efficacy studies performed under experimental and/or field conditions, the majority of agents belonging to these antimicrobial classes improved clinical parameters (clinical signs, lung lesions) and reduced performance losses due to M. hyopneumoniae infection. Antimicrobials may, however, not be able to prevent infection or to eradicate the bacterium from the respiratory tract. The decision to medicate should, therefore, be considered carefully. M. hyopneumoniae shows an intrinsic resistance against β–lactam antibiotics, sulfonamides and trimethoprim. A few reports have shown acquired antimicrobial resistance against some antibiotics, along with associated resistance mechanisms. The results of antimicrobial susceptibility testing are difficult to interpret in terms of treatment outcome, as no clinical breakpoints have been defined for M. hyopneumoniae .